Intrusion Detection Systems - Mancini, Luigi V.; Pietro, Roberto; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
In our world of ever-increasing Internet connectivity, there is an on-going threat of intrusion, denial of service attacks, or countless other abuses of computer and network resources. In particular, these threats continue to persist due to the flaws of current commercial intrusion detection systems (IDSs). Intrusion Detection Systems is an edited volume by world class leaders in this field. This edited volume sheds new light on defense alert systems against computer and network intrusions. It also covers integrating intrusion alerts within security policy framework for intrusion response, related case studies and much more. This volume is presented in an easy-to-follow style while including a rigorous treatment of the issues, solutions, and technologies tied to the field. Intrusion Detection Systems is designed for a professional audience composed of researchers and practitioners within the computer network and information security industry. It is also suitable as a reference or secondary textbook for advanced-level students in computer science. .
Approaches in Anomaly-based Network Intrusion Dete -- Formal Specification for Fast Automatic Profiling -- Learning Behavior Profiles from Noisy Sequences -- Correlation Analysis of Intrusion Alerts -- An Approach to Preventing, Correlating, and Predic -- Response: bridging the link between intrusion dete -- Intrusion Detection and Reaction: an Integrated Ap.
Keywords: Computer science; Computer organization; Computer communication systems; Computer security; Data structures (Computer science).; Data encryption (Computer science).; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computer Systems Organization and Communication Networks; Data Structures, Cryptology and Information Theory; Electronic books